1998
DOI: 10.1093/humupd/4.5.655
|View full text |Cite
|
Sign up to set email alerts
|

Sperm transport in the human female genital tract and its modulation by oxytocin as assessed by hysterosalpingoscintigraphy, hysterotonography, electrohysterography and Doppler sonography

Abstract: The transport function of the uterus and oviducts and its modulation by oxytocin has been examined using hysterosalpingoscintigraphy, recording of intrauterine pressure, electrohysterography and Doppler sonography of the Fallopian tubes. After application to the posterior vaginal fornix, a rapid (within minutes) uptake of the labelled particles into the uterus was observed during the follicular and during the luteal phase of the cycle in all patients. Transport into the oviducts, however, could only be demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
92
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(101 citation statements)
references
References 42 publications
1
92
0
8
Order By: Relevance
“…Возможны четыре механизма «первичного прохож-дения прогестерона в матку» при интравагинальном использовании микронизированного прогестерона: 1) прямая диффузия через ткани [31]; 2) пассаж прогестерона через цервикальный ка-нал из влагалища в полость матки [32];…”
Section: почему эндометрий в протоколах стимуляции яич-ников часто явunclassified
“…Возможны четыре механизма «первичного прохож-дения прогестерона в матку» при интравагинальном использовании микронизированного прогестерона: 1) прямая диффузия через ткани [31]; 2) пассаж прогестерона через цервикальный ка-нал из влагалища в полость матки [32];…”
Section: почему эндометрий в протоколах стимуляции яич-ников часто явunclassified
“…There is indirect evidence for a link between female orgasm and fertility (9,10,11,12). However, to date, the evidence is mixed and hotly disputed (13).…”
Section: Introductionmentioning
confidence: 99%
“…Female orgasm also causes patterns of brain activation and hormone release associated with increased uterine contractions, lower uterine pressure, and movement of semen into the uterus. Peristaltic uterine contractions transport sperm in rats, dogs, cows (Singer, 1973) and probably humans (Wildt et al, 1998) and appear to be caused both by a hormone released during orgasm and by stimulation of brain areas activated during orgasm. In women, orgasm activates the cingulate cortex and medial amygdala (Komisaruk et al, 2004), and electrical stimulation of these areas in experimental animals induces uterine contractions (Beyer et al, 1961;Setekleiv, 1964).…”
mentioning
confidence: 99%
“…Orgasm also activates the paraventricular nucleus (PVN; Komisaruk et al, 2004), and both PVN stimulation (Cross & Wakerley, 1977) and orgasm have been found to cause oxytocin release into the bloodstream (Blaicher et al, 1999;Carmichael et al, 1987;Carmichael et al, 1994). Oxytocin, in turn, induces uterine contractions (Knaus, 1950;Wildt et al, 1998), changes uterine pressure from outward to inward, and increases the transport of a semen-like fluid into the uterus and oviducts (Wildt et al, 1998).…”
mentioning
confidence: 99%